Insightful data visualization with SAS® Viya® - Schulz, Falko; Murphy, Travis (SAS Institute, 2020)
Elevate your storytelling with SAS Visual Analytics Data visualization is the gateway to artificial intelligence (AI) and big data. Insightful Data Visualization with SAS Viya shows how the latest SAS Viya tools can be used to create data visualizations in an easier, smarter, and more engaging way than ever before. SAS Visual Analytics combined with human creativity can produce endless possibilities. In this book, you will learn tips and techniques for getting the most from your SAS Visual Analytics investment. From beginners to advanced SAS users, this book has something for everyone. Use AI.
Includes bibliographical references
Keywords: SAS (Computer file); Graphic methods; Information visualization; Statistics -- Graphic methods; Méthodes graphiques; Visualisation de l'information; Statistique; Méthodes graphiques; graphs; Statistics; Graphic methods